Surface morphology and structure of nanocrystalline diamond films deposited in CH₄/H₂/Ar glow discharge plasma - Vyrovets, I.I.; Gritsyna, V.I.; Dudnik, S.F.; Opalev, O.A.; Reshetnyak, E.N.; Strel'nitskiy, V.E. (Functional Materials, 2009)
Diamond films of up to 12 μm thickness have been deposited onto single crystal silicon substrates by CVD method in CH₄/H₂/Ar glow discharge plasma stabilized by magnetic field. X-ray diffraction analysis and atomic force microscopy have shown the films consist of about 1 μm in diameter conglomerates of 30-40 nm average size diamond nanocrystals. The conglomerate size increases by a factor of 2 as the film thickness grows from 1.7 up to 11.7 μm. At the same time, the nanocrystallite size remains essentially unchanged. In the diamond films, texture, compressive residual stresses and high concentration of crystal structure defects have been revealed. Алмазні плівки товщиною до 12 мкм отримано на підкладках з монокристалічного кремнію методом газофазного осадження у CH₄/H₂/Ar плазмі тліючого розряду, стабілізованого магнітним полем. Методами рентгеноструктурного аналізу та атомно-силової мікроскопії встановлено, що плівки складаються з конгломератів діаметром - 1 мкм, утворених нанокристалами алмазу із середнім розміром 30-40 нм. 3 ростом товщини плівки від 1,7 до 11,7 мкм розмір конгломератів збільшується у 2 рази. При цьому розмір нанокристалів практично не змінюється. У плівках виявлено текстуру, залишкові напруження стиску та високий вміст дефектів кристалічної структури. Алмазные пленки толщиной до 12 мкм получены на подложках из монокристаллического кремния методом газофазного осаждения в CH₄/H₂/Ar плазме тлеющего разряда, стабилизированного магнитным полем. Методами рентгеноструктурного анализа и атомно-силовой микроскопии установлено, что пленки состоят из конгломератов диаметром -1 мкм, образованных нанокристаллами алмаза со средним размером 30-40 нм. С ростом толщины rтенки от 1,7 до 11,7 мкм размер конгломератов увеличивается в 2 раза. При этом размер нанокристаллов практически не меняется. В пленках выявлены текстура, остаточные напряжения сжатия и высокое содержание дефектов кристаллического строения.